Guru Efektif Dalam Pembelajaran Pendidikan Agama Islam - Musyaffa Rafiqie (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
Effective teachers will always look for better ways in teaching. There are four components that need to be considered for effective teachers. The four components are the first teacher having mastery of knowledge about teaching materials and teaching materials taught by both teachers having critical thinking skills and able to solve the problems that exist in the learning of the three teachers has the ability of knowledge about the characteristics of students and master the learning methods. And the four teachers have skills in teaching and can communicate well with students. Thus, the purpose of discussion from this research report is to describe the effective teacher.